Graded levels of Sesbania sesban and Leucaena leucocephala as supplements to teff straw fed to Ethiopian Menz sheep - Bonsi, M.L.K.; Osuji, P.O.; Nsahlai, I.V.; Tuah, A.K. (Cambridge University Press, 1994)
Two experiments were conducted to investigate the effect of supplementation with fodder tree leaves on the utilization of teff straw. This was aimed at testing the hypothesis that forage supplements (e.g. sesbania) that disappear faster from the rumen compared with those that disappear slowly (eg. leucaena) may elicit higher intakes of the basal diet. Experiment 1 investigated the effect of level (i.e. 0,200,300 and 400 g/kg dry matter (DM) intake) of leaves of Sesbania sesban or Leucaena leucocephala on the utilization of teff straw fed ad libitum. Seven sheep were given the seven diets in four periods following a partially balanced (7 X 4) cross-over design. In experiment 2, teff straw alone or supplemented with graded levels of sesbania (250, 350 and 450 g/kg DM intake), were fed to 16 sheep in a completely randomized block design. Intake, degradability, nitrogen (N) utilization, particulate and liquid passage rates were estimated. In experiment 1, protein source X protein level interaction was not significant. Supplementation increased intakes of total DM (P<0.05), organic matter (P<0.01) and N retention (P<0.01) but had no effect on the intake of teff straw. Supplementation with sesbania, but not with leucaena, increased (P<0.05) the apparent digestibility of DM. Both supplements increased (P<0.05) the fractional rate of passage from the rumen. In experiment 2, graded levels of sesbania increased DM intake (P<0.05), fractional rate of liquid outflow (P<0.05) and tended to increase the rate of degradation. It was concluded that the effect of fodder tree leaves on roughage intake is a function of their disappearance rate from the rumen.